Unsur Emosi Tokoh Utama dalam Novel Harga Sebuah Percaya Karya Tere Liye - Mutia Rahmi; Nurizzati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This article aims: (1) to describe the forms of emotion of the main character in the novel Harga Sebuah Percaya by Tere Liye Liye, (2) to describe the causes of the main character's emotions in the novel Harga Sebuah Percaya By Tere Liye Liye's, and (3) to describe the emotional impact the main character in the novel Harga Sebuah Percaya By Tere Liye. The Type of Research used in literary research with descriptive methods. The subject used in this study is the novel Harga Sebuah Percaya by Tere Liye. Based on the research, it was found that there are 2 forms of the main character's emotions in Tere Liye's Novel Price of a Belief, namely positive emotions and negative emotions. Positive emotions consisting of joy and happiness, cuteness, serenity, awe, hope and love. Negative emotions consist of disappointment, sadness, fear and anger. Factors that cause the main character's emotions are biological creatures, natural events, sounds and vibrations, attitudes and behavior and situations and conditions. The impact of the main character's emotions is to strengthen the spirit and interfere with social adjustment.